2006
DOI: 10.1363/3219206
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between HIV Risk Perception and Condom Use: Evidence from a Population-Based Survey in Mozambique

Abstract: CONTEXT: The relationship between individuals' perception of their risk for acquiring HIV and their use of condoms is poorly understood. Understanding this relationship is crucial to the development of effective strategies to fight HIV and AIDS. METHODS: Data from the Mozambique 2001 Adolescent and Young Adult Reproductive Health and Behavior Risk Survey are used to compare 15-24-year-olds' assessments of their HIV risk with assessments based on current and past sexual behavior. In bivariate and probit regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 22 publications
15
102
0
5
Order By: Relevance
“…Although we were not able to include social environment, psychological, and cultural factors in our analysis, evidence from other studies suggest that socio-cultural factors are the most common barriers to obtaining male condoms among sexually-experienced adolescents in Burkina Faso. [12][13][14][15][16][17][18][19][20][21][22][23][24] Strong cultural taboos are especially restrictive for sexually active women.…”
Section: Discussionmentioning
confidence: 99%
“…Although we were not able to include social environment, psychological, and cultural factors in our analysis, evidence from other studies suggest that socio-cultural factors are the most common barriers to obtaining male condoms among sexually-experienced adolescents in Burkina Faso. [12][13][14][15][16][17][18][19][20][21][22][23][24] Strong cultural taboos are especially restrictive for sexually active women.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the results regarding the skills of commercial sex workers will be useful to develop strategies and methods of health education to improve the condition of health and promote healthy living in this population living under fragile conditions. A previous study performed in Mozambique indicated that correct self-assessment regarding one's own risk of HIV/AIDS was necessary to change behaviour (Prata et al, 2006). We believe that educational messages to avoid risks should be passed to new as well as experienced commercial sex workers.…”
Section: Discussionmentioning
confidence: 85%
“…Numa perspetiva mais alargada de compreensão da exposição das pessoas ao risco de infeção pelo VIH/SIDA, encontramos constructos como a perceção de risco que é tida por muitos autores (e.g., Napper, Fisher, & Reynolds, 2012;Prata, Morris, Mazive, Vahidnia, & Stehr, 2006) como o fator principal para a compreensão do que motiva as pessoas a exporem-se às situações potencialmente perigosas relativas à contaminação pelo vírus. Contudo, a evolução do conhecimento sobre o padrão de transmissão do VIH/SIDA, nomeadamente o aumento significativo da incidência de casos de pessoas consumidoras de substâncias psicoativas, obrigou a que esta nova variável se juntasse à equação.…”
Section: Segundo O European Centre For Diseaseunclassified